Protein intake and urinary albumin excretion rates in the EURODIAB IDDM Complications Study - Toeller, M.; Buyken, Anette; Heitkamp, G.; Brämswig, S.; Mann, J.; Milne, R.; Gries, F. A.; Keen, H. (Diabetologia)

Relation of fibre intake to HbA 1c and the prevalence of severe ketoacidosis and severe hypoglycaemia - Buyken, Anette; Toeller, M.; Heitkamp, G.; Vitelli, F.; Stehle, P.; Scherbaum, W. A.; Fuller, J. H. (Diabetologia)

Carbohydrate sources and glycaemic control in Type 1 diabetes mellitus - Buyken, Anette; Toeller, M.; Heitkamp, G.; Irsigler, K.; Holler, C.; Santeusanio, F.; Stehle, P.; Fuller, J. H.; Group, the Eurodiab Iddm Complications Stu (Diabetic Medicine)

The Impact of Dietary Fat Composition on Serum Leptin Concentrations in Healthy Nonobese Men and Women - Kratz, Mario; von Eckardstein, Arnold; Fobker, Manfred; Buyken, Anette; Posny, Nicole; Schulte, Helmut; Assmann, Gerd; Wahrburg, Ursel (The Journal of Clinical Endocrinology & Metabolism)

Protein intake - new evidence for its role in diabetic nephropathy - Toeller, M; Buyken, Anette (Nephrology Dialysis Transplantation)

Das Modell der Salutogenese als Handlungsanleitung für haushaltsbezogene Bildung? Fragen und Folgerungen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

O Laboratório de Fontes Alternativas de Energia da UFRJ – LAFAE (Labor für alternative Energiequellen an der UFRJ) - Rosa, L. P.; Krauter, Stefan; Nascimento, J. L.; Sampaio, M.; Silva, N. F.; Araújo, M. P.; Petersen, R. C. (IX Congresso Brasileiro de Energia, Rio de Janeiro (Brasilien), 21.–22. Mai 2002, Band 4, S. 1780–1785.)

Data Warehouse in der Marktforschung - Analyse von Benutzeraktivitäten in virtuellen Welten - Schryen, Guido; Schoenen, Markus (Data Warehousing 2002)
Bei der Online-Marktforschung lässt sich mit Hilfe virtueller 3D-Welten das Konsumentenverhalten beobachten. Da die Struktur der dabei anfallenden Daten multidimensional ist und die marktforschungsrelevanten Anfragen eine hohe OLAP-Affinität aufweisen, wurde hierzu im Rahmen des Forschungsprojekts Benevit ein Data Warehouse konzipiert und realisiert. Im Rahmen einer Standardisierung der Protokollierung von Konsumentenaktivitäten und deren prototypischen Realisierung erwies sich der Data Warehouse/OLAP-Ansatz zur Speicherung, Analyse und Präsentation der Marktforschungsdaten als adäquates Instrumentenbündel.

x3Dogl: ein auf XML basierendes Web3D-System zur Darstellung interaktiver 3D-Szenen - Goetz, F.; Domik, Gitta (Informatiktage 2002)

Darstellung und Bewertung von Online und Offline Medien unter dem Gesichtspunkt nachhaltiger Ernährungsstile. Lehren und Lernen im haushaltsbezogenen Unterricht. - Bigga, Regine; Schack, Pirjo Susanne (Haushalt & Bildung)

A UML Profile for Real-Time Constraints with the OCL - Flake, Stephan; Müller, Wolfgang (Proceedings of the UML 2002 - The Unified Modeling Language)
This article presents a UML profile for an OCL extension that enables modelers to specify behavioral, state-oriented real-time constraints in OCL. In order to perform a seamless integration into the upcoming UML2.0 standard, we take the latest OCL2.0 metamodel proposal by Warmer et al. [22] as a basis. A formal semantics of our temporal OCL extension is given by a mapping to time-annotated temporal logics formulae. To give an example of the applicability of our extension, we consider a modeling approach for manufacturing systems called MFERT. We present a corresponding UML profile for that approach and combine both profiles for formal verification by real-time model checking.

Der Technikbegriff bei Rosa Luxemburg und seine Bedeutung für aktuelle techniksoziologische Fragen (Rosa Luxemburg’s Notion of Technology and Its Implications for Sociology of Technology) - Fuchs, Christian (Vorschein 22/23)

Nutrient intakes as predictors of body weight in European people with type 1 diabetes. - Toeller, M; Buyken, Anette; Heitkamp, G; Cathelineau, G; Ferriss, B; Michel, G; IDDM Complications Study Group, EURODIAB (Int J Obes Relat Metab Disord)

Glycemic index in the diet of European outpatients with type 1 diabetes: relations to glycated hemoglobin and serum lipids. - Buyken, Anette; Toeller, M; Heitkamp, G; Karamanos, B; Rottiers, R; Muggeo, M; Fuller, JH; IDDM Complications Study Group, EURODIAB (Am J Clin Nutr)

Salutogenese und haushaltsbezogene Bildung – didaktische Folgerungen - Schlegel-Matthies, Kirsten (Salutogenese und Ernährungsbildung. Abstracts des Workshops vom 9. und 10. März 2001)

Lebensstile von Jugendlichen und Umgang mit Geld. Folgerungen für haushaltsbezogene Bildung - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Factoring a binary polynomial of degree over one million - Bonorden, Olaf; von zur Gathen, Joachim; Gerhard, Jürgen; Müller, Olaf (ACM SIGSAM Bulletin)
On 22 May 2000, the factorization of a pseudorandom polynomial of degree 1 048 543 over the binary field Z 2 was completed on a 4-processor Linux PC, using roughly 100 CPU-hours. The basic approach is a combination of the factorization software BIPOLAR and a parallel version of Cantor's multiplication algorithm. The PUB-library (Paderborn University BSP library) is used for the implementation of the parallel communication.

Occlusion Culling for Virtual Environments based on the 3D-Sectorgraph - Klein, Jan; Fischer, Matthias (Proc. of 3. GI-Informatiktage 2001)
We present a new approximate occlusion-culling algorithm that in contrast to other algorithms, manages the objects of the scene in a 3D-sectorgraph. For generating a frame, as far as possible only the visible objects are rendered that can be found quickly by an edge of the graph. The algorithm allows a real-time navigation with over 20 frames per second in complex scenes consisting of over 10 millions of polygons. Moreover, approximation errors are very low.

Satellite Monitoring of Remote PV-Systems - Krauter, Stefan; Ochs, F.; Depping, T. (Proceedings of the 17th European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 22.–26. Oktober 2001, Band 3, S. 2598–2599)

Development of an All-in-one Solar Home System - Ochs, F.; Krauter, Stefan (Proceedings of the 17th European Photovoltaic Solar Energy Conference and Exhibition, München (Deutschland), 22.–26. Oktober 2001, Band 3, S. 2595–2597)

Jugend ohne ARBEITsLEHRE? Bilanz und Perspektiven schulischer Berufsorientierung. - Bigga, Regine (Arbeitslehre 2001. Bilanzen - Initiativen - Perspektiven.)

Customer-Oriented Systems Design through Virtual Prototyps - Flake, Stephan; Geiger, Christian; Müller, Wolfgang; Ruf, Jürgen (Proceedings of IEEE KMN 2001)
Rapid prototyping based on 3D models is well accepted for several applications. This article addresses the application of animated virtual 3D prototypes for the development of computer-based systems supporting early collaboration of the system designer with the external customer. Our methodology seamlessly integrates illustration through 3D animation with the main tasks of computer-based real-time systems development, i.e., implementation and verification. The approach is outlined by the example of the design of a flexible manufacturing system.
Keywords: Virtual prototyping; Animation; Collaboration; System analysis and design; Feedback; Application software; Power system modeling; Handicapped aids; Process design; Contracts

Carbohydrate sources and glycaemic control in Type 1 diabetes mellitus. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Irsigler, K; Holler, C; Santeusanio, F; Stehle, P; Fuller, JH (Diabet Med)

Developing Effective Navigation Techniques in Virtual 3D Environments - Volbracht, Sabine; Domik, Gitta (Virtual Environments 2000)

Optimization of Interblade Friction Damper - Panning, Lars; Sextro, Walter; Popp, Karl (International Gas Turbine & Aeroengine Congress & Exhibition, ASME)
the vibration amplitudes of bladed disk assemblies can be reduced significantly by means of friction damping devices such as shrouds, damping wires and interblade Friction dampers. in practice, interblade Friction dampers are applied in rotating arrangements with various geometries showing curved or flat surfaces like so-called wedge-shaped dampers. this paper is focusing on a computation method to predict the dynamical behaviour of turbine blades with Friction dampers including both, curved and wedge-shaped dampers with hertzian and non-herutian contact conditions, respectively. the presented computation method uses a 3d contact model to calculate the contact forces, including normal and tangential stiffnesses, roughness and microslip effects. the relative displacements in the contact area can be expressed by means of 6 dof of the blade platforms and 6 rigid body dof of the damper including translational and rotational displacements. the relative displacement of the Friction damper with respect to the adjacent blades can be derived from the contact kinematics of the blade-damper-blade system and the equations of motion of the Friction damper. thus, the model can be applied to investigate spatial motions of the bladed disk assembly including bending and torsional vibrations. a comparison of different Friction damper designs with respect to an optimal damper geometry and damper mass is presented. the advantages and disadvantages of each design will be discussed. experimental results are shown to validate the developed computation method.

Fünf vor zwölf und keinen Ausbildungsplatz. Eine Unterrichtsskizze zur Berufsorientierung. - Bigga, Regine (awt-info)

Prototyping einer Fahrzeug-steuerung in einer virtuellen 3D-Umgebung - Braatz, A.; Flake, Stephan; Müller, Wolfgang; Westkämper, E.
Prototyping mit 3D-Modellen in virtueller Umgebung ist eine kostengünstige Alternative zur Entwicklung von physikalischen Modellen und Mock-ups. Für einige Anwendungen ergeben sich erhebliche Vorteile durch die Validierung in einer virtuellen Umgebung. In diesem Artikel stellen wir den Einsatz einer 3D-Animation zur Entwicklung und zum Test einer Fahrzeugsteuerung vor. Basierend auf dem Prinzip der schrittweisen Verfeinerung kann die Steuerung zunächst nur unter Berücksichtigung der Kommunikation zwischen den Basiskomponenten entworfen werden. Im zweiten Schritt wird die Ansteuerung der Aktoren unter Auswertung der Sensoren berücksichtigt. Letztendlich ist das System unter Einflussnahme der physikalischen Größen zu validieren. Wir stellen die Schnittstelle exemplarisch anhand einer Steuerung für fahrerlose Transportfahrzeuge im Szenario eines holonischen Transportsystems vor.

Prevalence of chronic complications, metabolic control and nutritional intake in type 1 diabetes: comparison between different European regions. EURODIAB Complications Study group. - Toeller, M; Buyken, Anette; Heitkamp, G; Berg, G; Scherbaum, WA (Horm Metab Res)

Fiber intake, serum cholesterol levels, and cardiovascular disease in European individuals with type 1 diabetes. EURODIAB IDDM Complications Study Group. - Toeller, M; Buyken, Anette; Heitkamp, G; de Pergola, G; Giorgino, F; Fuller, JH (Diabetes Care)

Interkulturelle Bildung als Aufgabe haushaltsbezogenen Unterrichts - Schlegel-Matthies, Kirsten (Internationale Perspektiven in Hauswirtschaft und Haushaltswissenschaft. 20 Jahre Beirat. Dokumentations- und Diskussionsbeiträge)

Virtuelles Prototyping einer Robotersteuerung durch interaktive 3D-Simulation - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang

Visual Specification, Modeling, and Illustrations of Complex Systems - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang (Proceedings of HICSS-32)
This article introduces and discusses different innovative means for visual specification and animation of complex concurrent systems. It introduces the completely visual programming language Pictorial Janus (PJ) and its application in the customer-oriented design process. PJ implements a completely visual programming language with inherent animation facilities. The article outlines the transformation of purely visual PJ programs into textual imperative programming languages. The second part of the article investigates animated 3D-presentations and introduces a novel approach to an animated 3D programming language for interactive customer-oriented illustrations.
Keywords: Animation; Computer languages; Object oriented modeling; Collaboration; Process design; Graphical user interfaces; Jacobian matrices; Standardization; Feedback; Software prototyping

Scalable System for 3D Audio Raytracing - Müller, Wolfgang; Ullmann, F. (Proceedings IEEE International Conference on Multimedia Computing and Systems)
Though several approaches in sound processing are denoted as 3D audio very few of them generate high quality 3D audio information which allows listeners to exactly locate sound sources in three dimensional space. We present an approach to enhance sound by high quality 3D audio information through acoustic ray tracing where 3D audio is offline processed with digital filters of a head-related transfer function. The basic approach computes a fixed sound source for fixed listener. This approach is extended to generate 3D audio for moving listeners in interactive environments.
Keywords: Ray tracing; Loudspeakers; Motion pictures; Acoustic reflection; Ear; Digital filters; Parallel processing; Humans; Physics; Crosstalk

Relation of fibre intake to HbA1c and the prevalence of severe ketoacidosis and severe hypoglycaemia. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Vitelli, F; Stehle, P; Scherbaum, WA; Fuller, JH (Diabetologia)

An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Beller, Walter, “Logic in Mexico”, In: Santiago Ramirez (ed.), Mexican Studies in the History and Philosophy of Science, Kluwer: Dordrecht 1995 (= Boston Stud. Philos. Sci.; 172), 1–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Berufsorientierung in Zeiten der Krise: Thematisierung - Dethematisierung. - Bigga, Regine (Schule und Arbeitswelt. Zwischen Thematisierung und De-Thematisierung von Geschlecht.)

Anregungen für die Lehrplanarbeit hinsichtlich der Gleichstellung der Geschlechter. Lehrpläne für Mädchen und Jungen. - Bigga, Regine (Lisa-Jahrbuch)

Authoring Communicating Agents in Virtual Environments - Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the Annual Conference for the Computer Human Interaction)
3D-graphics popularity has steadily increased in a number of areas such as entertainment, scienti c vi- sualization, simulation, and virtual reality. Despite this rapid growth the authoring of animated 3D objects in virtual environments is stil l by no means trivial. This article presents new concepts of the animated 3D programming language SAM (Solid Agents in Motion) and its programming environment. In SAM, the main syntactic objects like agents, rules, and messages are represented as 3D objects. The design of a SAM pro- gram is supported by a dedicated 3D structure editor. The editor al lows the de nition and spatial arrange- ment of SAM agents in a 3D scene by direct manipu- lation. The paper gives a number of SAM examples, demonstrating the authoring of simple animated vir- tual 3D scenarios.

SAM - An Animated 3D Programming Language - Geiger, Christian; Müller, Wolfgang; Rosenbach, W. (Proceedings of the IEEE Symposium on Visual Languages)
This article presents the animated visual 3D programming language SAM (Solid Agents in Motion) for parallel systems specification and animation. A SAM program is a set of interacting agents synchronously exchanging messages. The agent's behaviour is specified by means of production rules with a condition and a sequence of actions each. Actions are linearly ordered and execute when matching a rule. In SAM, main syntactic objects like agents, rules, and messages are 3D. These objects can have an abstract and a concrete, solid 3D presentation. While the abstract representation is for programming and debugging, the concrete representation is for animated 3D end-user presentations. After outlining the concepts of SAM this article gives two programming examples of 3D micro worlds and an overview of the programming environment.
Keywords: Animation; Computer languages; Solids; Concrete; Application software; Virtual reality; Programming profession; Switches; Visualization; Debugging

Repeatability of three-day dietary records in the EURODIAB IDDM Complications Study. - Toeller, M; Buyken, Anette; Heitkamp, G; Milne, R; Klischan, A; Gries, FA (Eur J Clin Nutr)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).

Rademacher, Ulf: Der Europäische Betriebsrat. Die Richtlinie 94 / 45 / EG des Rates vom 22. 4. 1994 und ihre Umsetzung in nationales Recht; Nomos: Universitätsschriften Recht 1997 - Krimphove, Dieter (Recht der Arbeit (RdA))

How effective are 3D display modes? - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Proceedings of the ACM SIGCHI Conference on Human factors in computing systems)

Blinde Flecken in der Berufsorientierung im Rahmen der Arbeitslehre. Zusammenhang von Erwerbsarbeit und Hausarbeit fehlt nach wie vor. - Bigga, Regine (Hauswirtschaftliche Bildung)

Visual-Textual Prototyping of 4D Scenes - Dücker, M.; Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1997 IEEE Symposium on Visual Languages)
3D-graphics are becoming popular in a steadily increasing number of areas such as entertainment, scientific visualization, simulation, and virtual reality. Despite this rapid growth the generation of animated 3D scenes is by no means trivial. Since animated 3D objects evolve over time the authors denote these objects as 4D. The article presents a novel approach to the rapid prototyping of 4D models. They introduce the AAL (Animated Agent Layer) system. AAL is an interpreter-based approach covering a textual (AAL-PR) as well as a visual command language (AAL-VL) for the specification of the dynamics in 4D scenes. AAL provides support for different levels of abstraction: primitives, structured objects, animated objects, and animated (autonomous) agents.
Keywords: Prototypes; Layout; Animation; Command languages; Application software; Libraries; Virtual reality; Computer graphics; Hardware; Context modeling

Nutritional intake of 2868 IDDM patients from 30 centres in Europe. EURODIAB IDDM Complications Study Group. - Toeller, M; Klischan, A; Heitkamp, G; Schumacher, W; Milne, R; Buyken, Anette; Karamanos, B; Gries, FA (Diabetologia)

An Experimental Comparison of 3D Display Modes - Volbracht, S.; Domik, Gitta; Shahrbabaki, K.; Fels, G. (Proceedings of IEEE Visualization)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)